Filamentation and Self-Focusing of Electron Beams in Vacuum and Gas Diodes; Technical Physics Letters; Vol. 45, No. 4 - Oleshko V. I. Vladimir Ivanovich; Tarasenko V. F. Victor Fedotovich; Burachenko A. G. Aleksandr Gennadjevich; Nguyen Van Vu (2019, 2019)
Title screen